Trans-boundary variations of urban drought vulnerability and its impact on water resource management in Singapore and Johor, Malaysia - Chuah, Chong Joon (2019)
Low-latitude areas generally experience relatively large precipitation totals, but droughts/dry spells do occur periodically and are potentially hazardous in these regions - especially within rapidly developing urban settlements. These areas typically have high water demand and therefore may potentially be subjected to water scarcity. Effective local water resource management lowering risks and vulnerabilities to drought is thus paramount, and these policies may be affected in regions with national borders sharing a common transboundary water resource. In this study, we (a) quantify and identify drought episodes using the Palmer Drought Severity Index in the neighbouring equatorial regions of Singapore and Johor, Malaysia, and (b) qualitatively examine each region's drought impacts and consequent responses through archival research over the past fifty years. The data indicate that both frequencies and intensities of drought episodes in both Singapore and Johor have increased over time, suggesting greater exposure to this hazard. However, there are distinct variations in drought impacts in Singapore and Johor, and how each region addresses water resource management to drought with varying degrees of success. Despite the close geographical proximity, significant variations in regional adaptive capacities suggest that different drought vulnerabilities exist. We discuss the efficacy of drought responses over different time scales, and suggest that a combination of demand- and supply-side policies, especially in the long-term, should be considered to reduce vulnerability to this hazard.